Utilization of Management Tool In Monitoring of a Metro Project Considering Live Details : A Review - Vaibhav Mishra; Afzal Khan (International Journal of Scientific Research in Civil Engineering, 2021)
Masterminding and Scheduling are the basic in the tremendous establishment project like road and augmentation improvement, Metro rail projects as these are proposed for public government help. These exercises are have different accomplices and huge proportion of money, resources are contributed. Less than ideal orchestrating and booking prompts loss of resources, extension in project cost and awful deferments. However, on account of the PC and programming headway, it now possible to plan these errands using programming takes after Primavera P6 and Microsoft office project. In this paper we are presenting review of literatures related to scheduling and monitoring of project using management tool.
Keywords: Primavera P6 Web; Bhopal Metro; Planning; Scheduling; Monitoring And Tracking